Nano high-entropy alloy as well as preparation method and application thereof
By using the idea of chemical synthesis of liquid metal under mild conditions, the problem of difficult to prepare multi-main nano high-entropy alloys in the prior art is solved, and high purity and excellent electrical properties are achieved, suitable for extreme environments. The wide temperature range strain material of the sensor.
Patent Information
- Application Number
- CN202411248773.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to prepare refractory multi-main nano high-entropy alloys under mild conditions, and the traditional method is not suitable for the preparation of refractory multi-main nano high-entropy alloys, and lacks wide-temperature domain strain sensing performance in extreme environments. Research.
By dissolving the metal precursor salt in a solvent to form a mixed solution of metal precursor, reacting and drying, and then annealing under an Ar/H2 atmosphere to form a nano-high entropy alloy. The chemical synthesis idea of liquid metal is achieved at 800-1000°C Nanoization of refractory metals.
Achieve the preparation of high-purity, uniform scale refractory multi-main nano high-entropy alloys under mild conditions, with excellent electrical and sensing properties, suitable for sensors in extreme environments, showing rapid and sensitiveness in a wide temperature domain Strain response.
Smart Images

Figure CN119282126A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano high entropy alloys, and in particular relates to a nano high entropy alloy, a preparation method and an application thereof. Background Art
[0002] Entropy-stable alloys, also known as high-entropy alloys, are alloys formed by five or more metals in equal or approximately equal amounts, with unique crystal structures and chemical compositions. In order to maintain flexibility in alloy design, the researchers relaxed the definition of high-entropy alloys and the requirement for equal atomic ratios, so ΔS mix All alloy systems with >1.5R can be defined as high entropy alloys. Since being proposed in 2004, high entropy alloys have received widespread attention. They have excellent mechanical properties, high temperature stability, corrosion resistance and good electrical properties. They are used in aerospace, transportation, biomedical materials, catalysis and other fields, especially in extreme environment sensing. They have great application potential. Among them, refractory alloys are very attractive candidate materials for use at extremely high temperatures. However, the development of alloys of this type of material has been slow and there are still some challenges.
[0003] At present, the preparation methods of refractory alloys are mostly based on traditional powder metallurgy, vacuum arc melting and other methods. Although these methods can prepare high-purity and complex-shaped refractory alloys, they have problems such as high composition and complex equipment, and are not suitable for the preparation of refractory multi-principal component nano-high entropy alloys. At present, there is still a lack of methods for synthesizing refractory multi-principal component nano-high entropy alloys under mild conditions. Therefore, it is urgent to seek methods to synthesize refractory multi-principal component nano-high entropy alloys under mild conditions to solve the above problems and explore their wide temperature range strain sensing performance under extreme environments. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a nano high entropy alloy, a preparation method and its application, which can realize the preparation of refractory multi-principal component nano high entropy alloy under mild conditions. The formed refractory multi-principal component nano high entropy alloy has high purity, uniform scale, high temperature resistance, excellent electrical properties and sensing properties, and is expected to be used as a sensitive material in sensors for extreme environments.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a nano high entropy alloy, comprising:
[0007] Step 1, dissolving a metal precursor salt in a solvent to prepare a metal precursor mixed solution;
[0008] Step 2, the metal precursor mixed solution is reacted to obtain a metal precursor homogeneous solution;
[0009] Step 3, drying the metal precursor homogeneous solution to obtain a dried metal precursor powder;
[0010] Step 4, annealing the dried metal precursor powder at 800-1100° C. in an Ar / H2 atmosphere to form a nano high entropy alloy;
[0011] The metal precursor salt is selected from at least four of ammonium molybdate, ammonium tungstate, ammonium niobate, niobium oxalate, tantalum ethoxide, tantalum chloride, gallium nitrate, gallium chloride, indium nitrate, indium chloride, tin chloride, stannous chloride, sodium nitrate, potassium nitrate, ammonium nitrate, calcium nitrate, lead nitrate, cerium nitrate, iron nitrate, cobalt nitrate, nickel nitrate, manganese nitrate, cadmium nitrate, silver nitrate, zinc nitrate, bismuth nitrate, praseodymium nitrate, copper nitrate, palladium nitrate, aluminum nitrate, samarium nitrate, uranium nitrate and europium nitrate.
[0012] Optionally, the flow ratio of Ar to H2 is 1:1.
[0013] Optionally, in step 1, the solvent is selected from at least one of water, methanol and ethanol.
[0014] Optionally, in step 1, the molar fraction of each metal precursor salt is 15% to 42%.
[0015] Optionally, in step 2, the reaction is carried out with stirring at 40 to 80°C.
[0016] Optionally, in step 3, the drying is oven drying or freeze drying; the drying conditions are 80-150°C and the time is 12-24 hours; the freeze drying temperature is -60°C to -40°C and the time is 12-24 hours.
[0017] Optionally, in step 4, the annealing time is 1 to 4 hours.
[0018] A nano high entropy alloy is prepared by the method for preparing the nano high entropy alloy described in any one of the embodiments of the present invention.
[0019] The nano high entropy alloy described in the present invention is used to prepare wide temperature range strain materials.
[0020] The nano high entropy alloy described in the present invention is used to prepare a wide temperature range strain sensor.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] Different from the traditional industrial method, the chemical synthesis of refractory metals assisted by liquid metals uses the characteristic of negative mixing enthalpy of liquid metals to achieve the transformation from metal precursors to nano refractory alloys under mild conditions (800-1000°C). A variety of metal salts are fully mixed and reacted in a solvent to form a homogeneous metal salt mixed solution, which is beneficial to the formation of a uniform single-phase solid solution during high-temperature annealing and avoids the formation of fragile intermetallic compounds; in addition, this method can directly synthesize nano-scale alloys without the need for nano-sizing with the help of other methods. The present invention provides ideas for the preparation of refractory multi-principal nano high-entropy alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0024] Figure 1 This is a SEM image of the MoWNbGa nano high entropy alloy prepared in Example 1;
[0025] Figure 2 This is the EDS image of the MoWNbGa nano high entropy alloy prepared in Example 1;
[0026] Figure 3 The XRD pattern of the MoWNbGa nano high entropy alloy prepared in Example 1;
[0027] Figure 4 This is an atomic ratio diagram of the MoWNbGa nano high entropy alloy prepared in Example 1;
[0028] Figure 5 XRD pattern of the MoWNbGa alloy prepared in Comparative Example 1;
[0029] Figure 6 XRD pattern of the MoWNbGa alloy prepared in Comparative Example 2;
[0030] Figure 7 TEM image of MoWNbIn nano high entropy alloy prepared in Example 2
[0031] Figure 8 This is the EDS image of the MoWNbIn nano high entropy alloy prepared in Example 2;
[0032] Fig. 9 XRD pattern of MoWNbIn nano high entropy alloy prepared in Example 2;
[0033] Fig.10 TEM image of the MoWNbGaIn nano high entropy alloy prepared in Example 3;
[0034] Fig.11 This is the EDS image of the MoWNbGaIn nano high entropy alloy prepared in Example 3;
[0035] Fig.12 XRD pattern of MoWNbGaIn nano high entropy alloy prepared in Example 3;
[0036] Fig.13 This is a low temperature strain response curve of the MoWNbGa nano high entropy alloy prepared in Example 1 at -190°C;
[0037] Fig.14 This is a high temperature strain response curve of the MoWNbGa nano high entropy alloy prepared in Example 1 at 1000°C. DETAILED DESCRIPTION
[0038] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0039] The method for preparing the nano high entropy alloy of the present invention comprises the following steps:
[0040] Step 1, taking a metal precursor salt and completely dissolving it in water or a water-alcohol mixed solution at room temperature to prepare a metal precursor mixed solution;
[0041] Step 2, the metal precursor mixed solution is reacted under stirring conditions at 40 to 80° C. for 1 to 4 hours to obtain a metal precursor homogeneous solution;
[0042] Step 3, the homogeneous metal precursor solution after the complete reaction is thermally dried at 80 to 150° C., or freeze-dried at -60 to -40° C. for 12 to 24 hours to remove the solvent to obtain a dried precursor powder;
[0043] Step 4, annealing the dried metal precursor powder at 800-1100° C. in an Ar / H 2 atmosphere for 1-4 hours to finally form a refractory multi-principal element nano high entropy alloy.
[0044] In step 1, the metal precursor salt is selected from at least four of ammonium molybdate, ammonium tungstate, ammonium niobate, niobium oxalate, tantalum ethoxide, tantalum chloride, gallium nitrate, gallium chloride, indium nitrate, indium chloride, tin chloride, stannous chloride, sodium nitrate, potassium nitrate, ammonium nitrate, calcium nitrate, lead nitrate, cerium nitrate, iron nitrate, cobalt nitrate, nickel nitrate, manganese nitrate, cadmium nitrate, silver nitrate, zinc nitrate, bismuth nitrate, praseodymium nitrate, copper nitrate, palladium nitrate, aluminum nitrate, samarium nitrate, uranium nitrate and europium nitrate.
[0045] In step 1, the solvent is water, methanol, ethanol or a mixture thereof.
[0046] In step 1, the molar fraction of each metal precursor salt is 15% to 42%.
[0047] In step 2, the reaction condition is stirring at 40-80°C.
[0048] In step 3, the drying method is drying or freeze drying, the drying conditions are 80-150° C.; the freeze drying temperature is -60° C. to -40° C., and the time is 12-24 hours.
[0049] In step 4, the annealing time is 1 to 4 hours.
[0050] The nano high entropy alloy is obtained by the preparation method.
[0051] Experiments have shown that the nano high entropy alloy material prepared by the present invention has a fast and sensitive response to strain in a wide temperature range of -190°C to 1000°C, confirming the application potential of the material in extreme environment sensing. Therefore, the nano high entropy alloy of the present invention is used to prepare wide temperature range strain materials. In addition, the nano high entropy alloy of the present invention can be used to prepare wide temperature range strain sensors.
[0052] Embodiment 1:
[0053] Step 1, respectively taking 0.02 mmol of ammonium molybdate, ammonium tungstate, 0.17 mmol of ammonium niobate and 0.1 mmol of gallium chloride and completely dissolving them in deionized water at room temperature to prepare a metal salt mixed solution;
[0054] Step 2, the metal salt mixed solution is stirred at room temperature for 2 hours, and then reacted at 60° C. for 2 hours to form a metal precursor homogeneous solution;
[0055] Step 4, the homogeneous metal precursor solution after the complete reaction is dried at 80° C. to remove excess solvent for 12 hours;
[0056] Step 6: After drying, the precursor powder is annealed in an Ar / H2 atmosphere at 800°C for 2 hours, wherein the flow ratio of Ar to H2 is 1:1. Finally, a MoWNbGa nano high entropy alloy is formed.
[0057] The SEM image of the MoWNbGa nano high entropy alloy obtained in Example 1 of the present invention is as follows: Figure 1 As shown, from Figure 1 It can be seen that the MoWNbGa nano high entropy alloy presents a nanoparticle agglomeration structure, which is consistent with the prediction. Figure 2 As shown, the element distribution of Mo, W, Nb, and Ga is shown (see Figure 2Figures a, b, c and d) in the figure confirm the existence of the four elements; the XRD pattern of MoWNbGa nano high entropy alloy is shown in Figure 3 As shown, from Figure 3 It can be seen that the synthesized material is a BCC phase MoWNbGa alloy, and there are no other phases and intermetallic compounds, indicating that the synthesized MoWNbGa nano high entropy alloy is a single solid solution, and proves the successful preparation of MoWNbGa nano high entropy alloy; XPS obtained atomic such as Figure 4 As shown, the atomic ratio of Mo:W:Nb:Ga is 42:23:20:15.
[0058] Comparative Example 1:
[0059] Step 1, respectively taking 0.02 mmol of ammonium molybdate, ammonium tungstate, 0.17 mmol of ammonium niobate and 0.1 mmol of gallium chloride and completely dissolving them in deionized water at room temperature to prepare a metal salt mixed solution;
[0060] Step 2, the metal salt mixed solution is stirred at room temperature for 2 hours, and then reacted at 60° C. for 2 hours to form a metal precursor homogeneous solution;
[0061] Step 4, the homogeneous metal precursor solution after the complete reaction is dried at 80° C. to remove excess solvent for 12 hours;
[0062] Step 6: The precursor powder obtained after drying is annealed in an Ar / H2 atmosphere at 800°C for 2h, wherein the H2 concentration is 10%.
[0063] The XRD pattern of the material obtained in Comparative Example 1 is as follows: Figure 5 As shown, the results show phase separation, which is affected by the hydrogen concentration and no single-phase alloy is generated under this condition.
[0064] Comparative Example 2:
[0065] Step 1, respectively taking 0.02 mmol of ammonium molybdate, ammonium tungstate, 0.17 mmol of ammonium niobate and 0.1 mmol of gallium chloride and completely dissolving them in deionized water at room temperature to prepare a metal salt mixed solution;
[0066] Step 2, the metal salt mixed solution is stirred at room temperature for 2 hours, and then reacted at 60° C. for 2 hours to form a metal precursor homogeneous solution;
[0067] Step 4, the homogeneous metal precursor solution after the complete reaction is dried at 80° C. to remove excess solvent for 12 hours;
[0068] Step 6: The precursor powder obtained after drying is annealed in an Ar / H2 atmosphere at 800°C for 1 hour, wherein the H2 concentration is 20%.
[0069] The XRD pattern of the material obtained in Comparative Example 2 is as follows: Figure 6 As shown, the results show phase separation. Affected by the holding time, no single-phase alloy is generated under this condition.
[0070] Embodiment 2:
[0071] Step 1, taking 0.1 mmol of ammonium molybdate, ammonium tungstate, ammonium niobate, and indium chloride respectively and completely dissolving them in deionized water at room temperature to prepare a metal salt mixed solution;
[0072] Step 2, the metal salt mixed solution is stirred at room temperature for 2 hours, and then reacted at 60° C. for 2 hours to form a metal precursor homogeneous solution;
[0073] Step 4, the homogeneous metal precursor solution after the complete reaction is dried at 80° C. to remove excess solvent for 12 hours;
[0074] Step 6: After drying, the precursor powder is annealed in an Ar / H2 atmosphere at 1000°C for 2 hours, wherein the flow ratio of Ar to H2 is 1:1. Finally, a refractory multi-principal element nano high entropy alloy is formed.
[0075] The TEM image of the MoWNbIn nano high entropy alloy obtained in Example 2 of the present invention is as follows: Figure 7 As shown, from Figure 7 It can be seen that the MoWNbIn nano high entropy alloy presents a nanoparticle agglomeration structure, which is consistent with the prediction. Figure 8 As shown, the element distribution of four elements, Mo, W, Nb, and In, is shown in Figure 8 Figures a, b, c and d) in the figure confirm the existence of the four elements; the XRD pattern of MoWNbIn nano high entropy alloy is shown in Fig. 9 As shown, from Fig. 9 It can be seen that the synthesized material is a BCC phase MoWNbIn alloy, and there are no other phases and intermetallic compounds, which indicates that the synthesized MoWNbIn nano high entropy alloy is a single solid solution, and proves the successful preparation of MoWNbIn nano high entropy alloy.
[0076] Embodiment 3:
[0077] Step 1, taking 0.1 mmol of ammonium molybdate, ammonium tungstate, ammonium niobate, gallium chloride, and indium chloride respectively and completely dissolving them in deionized water at room temperature to prepare a metal salt mixed solution;
[0078] Step 2, the metal salt mixed solution is stirred at room temperature for 2 hours, and then reacted at 60° C. for 2 hours to form a metal precursor homogeneous solution;
[0079] Step 4, the homogeneous metal precursor solution after the complete reaction is dried at 80° C. to remove excess solvent for 12 hours;
[0080] Step 6: After drying, the precursor powder is annealed in an Ar / H2 atmosphere at 1000°C for 2 hours, wherein the flow ratio of Ar to H2 is 1:1. Finally, a MoWNbGaIn nano high entropy alloy is formed.
[0081] The TEM image of the MoWNbGaIn nano high entropy alloy obtained in Example 3 of the present invention is as follows: Fig.10 As shown, from Fig.10 It can be seen that the MoWNbGaIn nano high entropy alloy presents a nanoparticle agglomeration structure, which is consistent with the prediction. Fig.11 As shown, the element distribution of five elements, Mo, W, Nb, Ga, and In, is shown in Fig.11 Figures a, b, c, d and e) in the figure confirm the existence of the four elements; the XRD pattern of MoWNbGaIn nano high entropy alloy is shown in Fig.12 As shown, from Fig.12 It can be seen that the synthesized material is a BCC phase MoWNbGaIn alloy, and there are no other phases and intermetallic compounds, indicating that the synthesized MoWNbGaIn nano-high entropy alloy is a single solid solution, and proves the successful preparation of MoWNbGaIn nano-high entropy alloy.
[0082] See also Fig.13 and Fig.14 The MoWNbGa nano high entropy alloy of specific implementation example 1 was tested for its wide temperature range strain performance, including large strain tests at minus 190°C and 1000°C. The results showed that the material has a fast and sensitive response to strain at both minus 190°C and 1000°C, confirming the application potential of the material in extreme environment sensing.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nano high entropy alloy, characterized in that: include: Step 1, dissolving a metal precursor salt in a solvent to prepare a metal precursor mixed solution; Step 2, the metal precursor mixed solution is reacted to obtain a metal precursor homogeneous solution; Step 3, drying the metal precursor homogeneous solution to obtain a dried metal precursor powder; Step 4, annealing the dried metal precursor powder at 800-1100° C. in an Ar / H2 atmosphere to form a nano high entropy alloy; The metal precursor salt is selected from at least four of ammonium molybdate, ammonium tungstate, ammonium niobate, niobium oxalate, tantalum ethoxide, tantalum chloride, gallium nitrate, gallium chloride, indium nitrate, indium chloride, tin chloride, stannous chloride, sodium nitrate, potassium nitrate, ammonium nitrate, calcium nitrate, lead nitrate, cerium nitrate, iron nitrate, cobalt nitrate, nickel nitrate, manganese nitrate, cadmium nitrate, silver nitrate, zinc nitrate, bismuth nitrate, praseodymium nitrate, copper nitrate, palladium nitrate, aluminum nitrate, samarium nitrate, uranium nitrate and europium nitrate.
2. The method for preparing nano high entropy alloy according to claim 1, characterized in that: The flow ratio of Ar to H2 is 1:
1.
3. The method for preparing a nano high entropy alloy according to claim 1 or 2, characterized in that: In step 1, the solvent is selected from at least one of water, methanol and ethanol.
4. The method for preparing a nano high entropy alloy according to claim 1 or 2, characterized in that: In step 1, the molar fraction of each metal precursor salt is 15% to 42%.
5. The method for preparing a nano high entropy alloy according to claim 1 or 2, characterized in that: In step 2, the reaction is carried out under stirring at 40-80°C.
6. The method for preparing a nano high entropy alloy according to claim 1 or 2, characterized in that: In step 3, the drying is drying or freeze drying; The drying condition is 80-150℃ and the time is 12-24h; The freeze-drying temperature is -60℃ to -40℃, and the time is 12 to 24 hours.
7. The method for preparing a nano high entropy alloy according to claim 1 or 2, characterized in that: In step 4, the annealing time is 1 to 4 hours.
8. A nano high entropy alloy, characterized in that: The nano high entropy alloy is prepared by the method for preparing the nano high entropy alloy according to any one of claims 1 to 7.
9. Use of the nano high entropy alloy according to claim 8 for preparing wide temperature range strain materials.
10. Use of the nano high entropy alloy according to claim 8 in preparing a wide temperature range strain sensor.
Citation Information
Patent Citations
Preparation method of nanoscale multi-element alloy
CN111545767A
Superhard wear-resistant refractory high-entropy alloy film and preparation method thereof
CN116516228A
Nanoscale refractory high-entropy alloy powder and preparation method thereof
CN118321567A